Study of the elastic properties of the lithium tantalate crystal by the Brillouin laser light scattering - BŁACHOWICZ, T. (Archives of Acoustics, 2000)
This article is dedicated to prof. J. Ranachowski The preparation of an experiment is described and measured values of elastic constants of the piezoelectric LiTaO3 crystal, which belongs to the rhomboedral symmetry system, are given. As the experimental method, the Brillouin laser light scattering was applied and the constants from the hypersonic range of frequencies were measured. Appropriate conditions for the experimental configurations were determined by the use of a formalism based on the looking for eigenvalues of a so-called "characteristic matrix" which is a function of direction of the acoustic wave propagation and the elastic constants of the medium. Not all the measurement results are in full agreement with calculations based on ultrasonic data. A dispersion in the velocity of the acoustic waves can be observed for some direction of propagation due to the elastic constant changes in the hypersonic frequency range.